Life and Understanding: The Origins of “Understanding” in Self-Organizing Nervous Systems - Yufik, Yan M.; Friston, Karl (Frontiers in Systems Neuroscience, 2016)
This article is motivated by the formulation of biotic self-organisation in (Friston, 2013), where the emergence of ‘life’ in coupled material entities (e.g., macromolecules) was predicated on bounded subsets that maintain a degree of statistical independence from the rest of the network. Boundary elements in such systems or units constitute a Markov blanket; separating the internal states of the unit from its surrounding states. In this paper, we ask whether Markov blankets operate in the nervous system and underlie the development of intelligence, enabling a progression from the ability to sense the environment to the ability to understand it. Markov blankets have been previously hypothesized to form in neuronal networks as a result of phase transitions that cause network subsets to fold into bounded assemblies, or packets (Yufik, 1998a). The ensuing neuronal packets hypothesis builds on the notion of neuronal assemblies (Hebb, 1949, 1980), treating such assemblies as flexible but stable biophysical structures capable of withstanding entropic erosion. In other words, structures that maintain their integrity under changing conditions. In this treatment, neuronal packets give rise to perception of ’objects’; i.e., quasi-stable (stimulus bound) groupings that are conserved over multiple presentations (e.g., the experience of perceiving ‘apple’ can be interrupted and resumed many times). Monitoring the variations in such groups enables the apprehension of behaviour; i.e., attributing to objects the ability to undergo changes without loss of self-identity. Ultimately, ‘understanding’ involves self-directed composition and manipulation of the ensuing ‘mental models’ that are constituted by neuronal packets, whose dynamics capture relationships among objects: that is, dependencies in the behaviour of objects under varying conditions. For example, movement is known to involve rotation of population vectors in the motor cortex (Georgopoulos et al, 1993; Georgopoulos et al, 1988). The neuronal packet hypothesis associates ‘understanding’ with the ability to detect and generate coordinated rotation of population vectors – in neuronal packets –in associative cortex and other regions in the brain. The ability to coordinate vector representations in this way is assumed to have developed in conjunction with the ability to postpone overt motor expression of implicit movement, thus creating a mechanism for prediction